1989
DOI: 10.1007/bf00199106
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical phenotyping of human solid tumors with monoclonal antibodies in devising biotherapeutic strategies

Abstract: A panel of 14 monoclonal antibodies (MoAbs) (4 raised against breast cancer, 6 against colon cancer and 4 against melanoma) were used to phenotype frozen sections of tumor biopsies obtained from 110 patients, by avidin-biotin-peroxidase complex techniques. We observed heterogeneity of antigen expression among the multiple metastatic lesions of single patients, as well as among tumor lesions from different patients with similar tumor histotypes. A wide range of cross-reactivity of anti-(breast-carcinoma) and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Heterogeneous antigen expression may also reduce therapeutic efficacy as non-antigen expressing cells will be left untargeted even if the saturation criteria (Γ<1, φ 2 <1) are achieved [100]. Combinations of antibodies against different antigens or therapeutics capable of initiating bystander effects may improve therapeutic efficacy in these cases [101,102].…”
Section: Antigen Selectionmentioning
confidence: 99%
“…Heterogeneous antigen expression may also reduce therapeutic efficacy as non-antigen expressing cells will be left untargeted even if the saturation criteria (Γ<1, φ 2 <1) are achieved [100]. Combinations of antibodies against different antigens or therapeutics capable of initiating bystander effects may improve therapeutic efficacy in these cases [101,102].…”
Section: Antigen Selectionmentioning
confidence: 99%
“…Double-label, 2-color, sequential IH studies comparing CA6 to CA125 demonstrated that MAbs DS6 and OC125, while showing extensive overlap, also show areas in which only 1 is expressed, providing additional, complementary coverage of the tumor. Such complementarity of TAA expression can have important clinical implications, whether for tailoring MAb-based cancer therapies as "cocktails" matched to a given tumor's antigenic phenotype (Liao et al, 1989;Oldham, 1991) or for devising panels of tumor markers to monitor tumor progression (Cane et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The additional breast tumor lines (BRXBr4 and BRXBrl) and two colon tumor lines (BRXCo6 and BRXCo3X) were established in our laboratory [26]. [30]. All cells were grown as monolayers in RPMI-1640 medium (Gibco, Grand Island, NY) with 10% heat-inactivated fetal bovine serum without antibiotics, The cultures were monitored for mycoplasma contamination using the Genprobe system (Gibco) and were found to be free of mycoplasma during the course of this study.…”
Section: Tissue Staining and Evaluationmentioning
confidence: 99%
“…Test antibody samples (5 ~tg/ml and 10 gg/tal) were added (100 gl/tube) and incubated for 30 min at 4°C. Immunofluorescent staining and flow cytometry were performed according to procedures previously described [30].…”
Section: Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation